Phanerozoic evolution of the West African Craton and its northern and western boundaries - (:unkn) unknown (My University, 2015)
The dynamic evolution of cratonic domains remains enigmatic as they are usually considered as stable through geological times. In this work, we unraveled the evolution of one of the largest cratonic area, the West African Craton (WAC), and its north and west boundaries (Anti-Atlas and Atlantic passive margin, respectively), through low-temperature thermochronology (apatite fission-track and (U-Th)/He thermochronology) and structural geology. The WAC was studied since its boundaries witnessed many different geological settings (platform, distal foreland, passive margin) during the Phanerozoic, making it a good candidate to evaluate the various driving forces acting on the craton.First, after a continuous Paleozoic subsidence, the craton records the most important cooling event between Late Jurassic and Early Cretaceous, postdating the onset of the Central Atlantic Ocean spreading. This event is unrelated to the sole passive margin in itself and affected both the craton (up to 800 km inland) and the mobile boundary in the north (Anti-Atlas and High Atlas). It represents kilometer-scale erosion that led to the deposition of thick detrital formations, the red beds, across the whole Saharan platform. This event is not characterized by shortening and is better explained through a mantle-related thermal anomaly during this exhumation. The thermal hypothesis explains the subsequent thermal subsidence undergone by the craton and its north boundary during the Aptian-Albian and the early stages of the Late Cretaceous.Second, from Late Cretaceous onward, dominant cooling trend has imprinted the thermal histories of the studied region, coevally with the onset of the Africa/Europe convergence.The High Atlas belt in Morocco is an accurate witness of the deformations occurring during Cenozoic times. We determined the precise tectonic schedule in the southern foreland of the belt and compared this evolution with the cratonic one. We show that the first Eocene tectonic
Keywords: African Research